Seasonal variability of the warm Atlantic water layer in the vicinity of the Greenland shelf break. Issue 23 (11th December 2014) - Grist, Jeremy P.; Josey, Simon A.; Boehme, Lars; Meredith, Michael P.; Laidre, Kristin L.; Heide‐Jørgensen, Mads Peter; Kovacs, Kit M.; Lydersen, Christian; Davidson, Fraser J. M.; Stenson, Garry B.; Hammill, Mike O.; Marsh, Robert; et al.
Abstract: The warmest water reaching the east and west coast of Greenland is found between 200 and 600 m. While important for melting Greenland's outlet glaciers, limited winter observations of this layer prohibit determination of its seasonality. To address this, temperature data from Argo profiling floats, a range of sources within the World Ocean Database, and unprecedented coverage from marine‐mammal borne sensors have been analyzed for the period 2002–2011. A significant seasonal range in temperature ( 1‐2°C) is found in the warm layer, in contrast to most of the surrounding ocean. The phase of the seasonal cycle exhibits considerable spatial variability, with the warmest water found near the eastern and southwestern shelf break toward the end of the calendar year. High‐resolution ocean model trajectory analysis suggests the timing of the arrival of the year's warmest water is a function of advection time from the subduction site in the Irminger Basin. Key Points: Seasonal temperature cycle found in the subsurface warm layer around Greenland There is a distinctive spatial variability to the phase of the seasonal cycle Phase of seasonal cycle related to water's travel time from the Irminger Sea